How Does Strategic Human Resource Management Impact on Employee Voice Behavior and Innovation Behavior With Mediating Effect of Psychological Mechanism - Li, Yunhe; Zhang, Li; Yan, Xin (Frontiers in Psychology, 2022)
Employees’ voice and innovation behaviors are an important source of organizational competitiveness. Scholars in the field of organizational behaviors have discussed how to increase the willingness of employees to engage in voice and innovation behaviors from a diversity of perspectives. Innovation has always been a strategic goal of organizations. To motivate employees to offer valuable advice and innovative ideas, organizations have to provide various incentive, feedback and supportive programs. Combined with the social exchange and social cognitive theories, this study presents an argument that the effective SHRM can gradually improve the self-efficacy, psychological contract, voice behaviors and innovation behaviors of employees, and further verifies the relationship among them. A sample of 553 employees was used and analyzed via PLS-SEM. The results showed that SHRM has a significant and positive impact on self-efficacy, psychological contract, voice behavior and innovation behavior; self-efficacy has a significant and positive impact on psychological contract, voice behavior and innovation behavior; psychological contract only has a significant and positive impact on innovation behavior, but not on voice behavior. Given the above research findings, this study gives some practical implications in the end.